m-Mode SVPWM Technique for Power Converters - Zhang, Bo.; Qiu, Dongyuan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents a novel control method for power converters, referred to as m-mode control. It provides an overview of traditional control methods for inverters - e.g. PWM and SVPWM - and the theory of the m-mode control method, while also discussing and applying m-mode control on various types of converters (including three-phase, nine-switch, five-leg and multi-level inverters, PWM rectifiers and modular multi-level converters). The book provides readers with sufficient background and understanding to delve deeper into the topic of SVPWM control. It is also a valuable guide for engineers and researchers whose work involves power converter control. .
Preface -- Introduction -- m-Mode Control Method -- 3-Mode Control for Three-phase Four-line Inverter -- 4-Mode Control for Three-phase Four-line Inverter -- 6-Mode Control for Nine-switch Inverter -- m-Mode Control for Multilevel Inverter -- m-Mode Control for Modular Multilevel Converter -- m-Mode Control for PWM Rectifier.
Keywords: Electric power production; System theory; Control theory; Electronic circuits; Electrical Power Engineering; Systems Theory, Control; Electronic Circuits and Systems